THE RELATIONSHIP BETWEEN NUMERICAL ABILITY, STUDENTS' ATTITUDE ON MATH LESSON, AND LEARNING CYLINES WITH MATHEMATICS LEARNING OUTCOMES - Khoirunisa Mahardini; Uus Kusdinar (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
Low student learning outcomes are associated with many factors. The relationship between numerical ability, students' attitudes on a math lesson, and learning lines is possibly related to learning outcomes. This research aims to determine the presence or absence of a positive and significant relationship between numerical ability, students' attitudes on a math lesson, and learning lines to mathematics learning outcomes in students class VIII of Junior High School (SMP) Muhammadiyah 9 Yogyakarta in Even Semester in Academic Year of 2016/2017. The population in this research was the students of VIII of SMP Muhammadiyah 9 Yogyakarta in 2016/2017, consisting of class VIII A, VIII B, VIII C, VIII D, VIII E, totaling 162 students. Class VIII E was selected as a class of research sample with a random sampling technique. The writer uses the questionnaire method to collect students' attitudes on math lessons and learning lines. The test method to get numerical ability data and math is resulting in learning. The research instrument: validity test, different power test, and reliability test. Test requirement analysis includes a test of normality, a test of linearity, and independence. The writer uses product-moment correlation analysis and multiple linear regression analysis to analyze the data. The results showed a positive and significant relationship between numerical ability, students' attitudes on a math lesson, and learning lines with mathematics learning outcomes in students class VIII of SMP Muhammadiyah 9 Yogyakarta in Even Semester in Academic Year of 2016/2017. It is showed by Fcount  Ftable is  with  and  with , with ,  and ,  dan .